2017
DOI: 10.4103/jcvjs.jcvjs_69_17
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel cervical laminectomy and fusion with posterior cervical cages

Abstract: Context:Cervical spondylotic myelopathy (CSM) is a progressive disease that can result in significant disability. Single-level stenosis can be effectively decompressed through either anterior or posterior techniques. However, multilevel pathology can be challenging, especially in the presence of significant spinal stenosis. Three-level anterior decompression and fusion are associated with higher nonunion rates and prolonged dysphagia. Posterior multilevel laminectomies with foraminotomies jeopardize the bone s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Kramer et al 21 confirmed this clinically and found that PCIDF was effective in obtaining multilevel circumferential fusion in patients deemed to be at high-risk in developing pseudoarthrosis. Bou Monsef and Siemionow 35 evaluated PCIDF as supplemental fixation in multilevel laminectomy for cervical spondylotic myelopathy and reported excellent patient outcomes and fusion rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kramer et al 21 confirmed this clinically and found that PCIDF was effective in obtaining multilevel circumferential fusion in patients deemed to be at high-risk in developing pseudoarthrosis. Bou Monsef and Siemionow 35 evaluated PCIDF as supplemental fixation in multilevel laminectomy for cervical spondylotic myelopathy and reported excellent patient outcomes and fusion rates.…”
Section: Discussionmentioning
confidence: 99%
“…Kramer et al 21 confirmed this clinically and found that PCIDF was effective in obtaining multilevel circumferential fusion in patients deemed to be at high-risk in developing pseudoarthrosis. Bou Monsef and Siemionow35…”
mentioning
confidence: 99%